Unraveling the impact of disrupted nucleocytoplasmic transport systems in C9orf72-associated ALS - McGoldrick, Philip; Robertson, Janice (Frontiers in Cellular Neuroscience, 2023)
Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are two adult-onset neurodegenerative diseases that are part of a common disease spectrum due to clinical, genetic, and pathological overlap. A prominent genetic factor contributing to both diseases is a hexanucleotide repeat expansion in a non-coding region of the C9orf72 gene. This mutation in C9orf72 leads to nuclear depletion and cytoplasmic aggregation of Tar DNA-RNA binding protein 43 (TDP-43). TDP-43 pathology is characteristic of the majority of ALS cases, irrespective of disease causation, and is present in approximately 50% of FTD cases. Defects in nucleocytoplasmic transport involving the nuclear pore complex, the Ran-GTPase cycle and nuclear transport factors have been linked with mislocalization of TDP-43. Here we will explore and discuss the implications of these system abnormalities of nucleocytoplasmic transport in C9orf72-ALS/FTD, as well as in other forms of familial and sporadic ALS.